Experiences of INIFAP hybrid corn seed producers in the Tlaxcala market - Larqué Saavedra, Bertha Sofía; Uzcanga Pérez, Nelda; Pérez del Ángel, Ana Lid; Sangerman Jarquín, Dora Maria; Islas Gutiérrez, Fabián; Rojas Martínez, Israel (Revista Mexicana de Ciencias Agrícolas, 2017)
This article to analyzes the diffi culties faced by producers of hybrid maize seeds and varieties of CEVAMEX-INIFAP in the state of Tlaxcala, after 12 years of being adopter of this technology generated by the CEVAMEX. It is a sociological, exploratory and descriptive study where the experiences of the adoptive producers were the fundamental element. It an individual cases producers, companies and firms were considered, all producers improved maize seed. The objectives of this work they were: identify the level of adoption according to an indicator developed on purpose for this investigation. Describe the experiences of producers in the production and sale of seeds and identify the variables that drive or hinder the adoption process. Thematic interviews were conducted, focal type meetings and questionnaires were applied. The topics discussed were availability of basic and registered seed, agronomic management and sales market to get certified seed producers. The information collected was compared between the various techniques used in the fi eld of information. The results suggest that the experiences of producers are framed by oligopolistic conditions the corn seed market is imposing in recent years, on situation that influences their decision to continue or discontinue the adoption process.